Enhancing Long-Term Memory Through Cognitive-Physical Training And Honey Supplementation: A Study On Qur’an-Memorizing Students At Al Ikhwan Assalam Junior High School - Miskah Afriani; Milna Chairunnisa; Rahmawati Tarigan (Journal of Innovative and Creativity, 2025)
Background: Long-term memory (LTM) plays a fundamental role in learning. Cognitive and nutritional interventions have been shown to influence memory encoding and consolidation, yet the short-term effectiveness of combining cognitive-physical exercises with honey intake remains underexplored. Objective: This study aims to evaluate the effectiveness of cognitive-physical intervention, honey consumption, and their combination in improving students’ LTM across three measurement points: day one, one week, and two weeks. Methods: A true experimental design was used involving 100 participants allocated into three treatment groups. Memory tasks were administered repeatedly. One-way ANOVA and Bonferroni Post Hoc tests were applied to examine between-group differences. Results: Cognitive-physical intervention significantly improved LTM on day one (p = 0.009) and day three (p = 0.003). Honey intake did not produce significant short-term effects, aligning with previous findings suggesting cognitive benefits of honey arise after 4–8 weeks of continuous consumption. The combined intervention did not yield a synergistic effect. These findings are consistent with mnemonic literature—such as the keyword mnemonic and method of loci—which reliably enhance encoding and retrieval processes. Conclusion: Cognitive-physical intervention is more effective than honey intake or the combined approach in improving short-term LTM. Future studies should adopt a 1–6 month longitudinal design to evaluate the long-term effects of honey consumption and potential interactions with cognitive and physical activities..